Viscosities of Liquid Cyclohexane and Decane at Temperatures between (303 and 598) K and Pressures up to 4 MPa Measured in a Dual-Capillary Viscometer - Liu,Z; Trusler,JPM; Bi,Q (Journal of Chemical and Engineering Data, 2015)
The viscosities of cyclohexane and decane arereported at temperatures between (303.15 and 598.15) K and atpressures of (0.1, 1, 2, 3 and 4) MPa. The experiments were carriedout with a dual-capillary viscometer that measures the ratio of theviscosities at temperature T and pressure p to that at a referencetemperature of 298.15 K and the same pressure. Absolute values ofthe viscosity were then obtained with an expanded relativeuncertainties at 95 % confidence of 3.0 % by combining themeasured ratios with literature values of the viscosity at the referencetemperature.